2000
DOI: 10.1038/sj.bmt.1702392
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic peripheral blood stem cell transplantation using a fludarabine-based low intensity conditioning regimen for malignant lymphoma

Abstract: Summary:Relapse is a serious complication following high-dose therapy and autologous bone marrow transplantation (ABMT) for malignant lymphoma (ML). Allogeneic transplantation (alloSCT) is a therapeutic option. However, it is associated with a high incidence of transplantrelated organ toxicity and mortality. We recently reported fast engraftment and minimal transplantrelated toxicity, using fludarabine-based conditioning with reduced amounts of chemotoxic drugs prior to alloSCT. We now present our experience w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(97 citation statements)
references
References 54 publications
6
90
0
1
Order By: Relevance
“…23,24 NRM is lower after RIC, in the range of 20-35%, which is still higher than NRM after RIC in AML/myelodysplastic syndromes. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] This is possibly related to patients with lymphoma been older and more heavily treated at the time of SCT including a high incidence of prior autologous SCT. In the current study NRM was relatively low after FT and FB2, both 24%, similar to RIC regimens, whereas it was 54% after FM which is more similar to MAC regimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 NRM is lower after RIC, in the range of 20-35%, which is still higher than NRM after RIC in AML/myelodysplastic syndromes. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] This is possibly related to patients with lymphoma been older and more heavily treated at the time of SCT including a high incidence of prior autologous SCT. In the current study NRM was relatively low after FT and FB2, both 24%, similar to RIC regimens, whereas it was 54% after FM which is more similar to MAC regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Survival rates in the range of 20-52% have been reported in other, smaller studies depending on patient characteristics at SCT. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Chemo-refractory disease is the most important predicting factor for survival across all studies. However, a small subset of patients with refractory lymphoma can achieve long-term survival with allogeneic SCT with both MAC and RIC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Certain toxic side effects reported after RIC were less prevalent in treosulfan-based transplants or did not occur in these patients. Although reduced-dose combinations with BU may still lead to severe hepatic toxicity 51 or to VOD, 39,52 the liver toxicity (alanine transaminase/aspartate aminotransferase elevation) seen with treosulfan was transient and did not exceed grade III. 40 No VOD occurred in the patients treated with treosulfan.…”
Section: Engraftment and Chimerismmentioning
confidence: 99%
“…This allowed the extension of allo-HCT to older patients or those with comorbidities and patients whose disease had progressed or relapsed after auto-HCT. 30,31 Although an early EBMT registry study reported disappointing outcomes for patients with high-grade NHL who underwent RIC allo-HCT with high rates of relapse (79% at 2 years), 32 recent trials in DLBCL have demonstrated the efficacy of this approach mainly in patients with chemosensitive disease 23,28,[32][33][34][35][36] (Table 2).…”
Section: Allo-hct With Non-myeloablative or Ricmentioning
confidence: 99%